Tuning the Photophysics of Two-Arm Bis[(dimethylamino)styryl]benzene Derivatives by Heterocyclic Substitution - Letizia Mencaroni; Alessio Cesaretti; Benedetta Carlotti; Martina Alebardi; Fausto Elisei; Ana Ratković; Irena Škorić; Anna Spalletti (Molecules, 2022)
The identification of novel molecular systems with high fluorescence and significant non-linear optical (NLO) properties is a hot topic in the continuous search for new emissive probes. Here, the photobehavior of three two-arm bis[(dimethylamino)styryl]benzene derivatives, where the central benzene was replaced by pyridine, furan, or thiophene, was studied by stationary and time-resolved spectroscopic techniques with ns and fs resolution. The three molecules under investigation all showed positive fluorosolvatochromism, due to intramolecular charge-transfer (ICT) dynamics from the electron-donor dimethylamino groups, and significant fluorescence quantum yields, because of the population of a planar and emissive ICT state stabilized by intramolecular hydrogen-bond-like interactions. The NLO properties (hyperpolarizability coefficient and TPA cross-section) were also measured. The obtained results allowed the role of the central heteroaromatic ring to be disclosed. In particular, the introduction of the thiophene ring guarantees high fluorescent quantum yields irrespective of the polarity of the medium, and the largest hyperpolarizability coefficient because of the increased conjugation. An important and structure-dependent involvement of the triplet state was also highlighted, with the intersystem crossing being competitive with fluorescence, especially in the thiophene derivative, where the triplet was found to significantly sensitize molecular oxygen even in polar environment, leading to possible applications in photodynamic therapy.